Proceedings of the ACM SIGMETRICS/international Conference on Measurement and Modeling of Computer Systems 2013
DOI: 10.1145/2465529.2465549
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic optimal tree hopping for RFID identification

Abstract: Radio Frequency Identification (RFID) systems are widely used in various applications such as supply chain management, inventory control, and object tracking. Identifying RFID tags in a given tag population is the most fundamental operation in RFID systems. While the Tree Walking (TW) protocol has become the industrial standard for identifying RFID tags, little is known about the mathematical nature of this protocol and only some ad-hoc heuristics exist for optimizing it. In this paper, first, we analytically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…We implemented and compared the performance of FRIP with nine prior tag identification protocols, namely the 3 nondeterministic (Aloha [21], BS [22], and ABS [23]), the 4 deterministic (TH [17], TW [24], ATW [25], and STT [26]), and the 2 hybrid protocols (MAS [27] and ASAP [28]). We did not compare FRIP with FNFRA [29] because the two protocols address different problems: FNFRA focuses on making reader scheduling process fair while FRIP focuses on making the tag identification process fair.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We implemented and compared the performance of FRIP with nine prior tag identification protocols, namely the 3 nondeterministic (Aloha [21], BS [22], and ABS [23]), the 4 deterministic (TH [17], TW [24], ATW [25], and STT [26]), and the 2 hybrid protocols (MAS [27] and ASAP [28]). We did not compare FRIP with FNFRA [29] because the two protocols address different problems: FNFRA focuses on making reader scheduling process fair while FRIP focuses on making the tag identification process fair.…”
Section: Resultsmentioning
confidence: 99%
“…Existing RFID identification protocols mostly focus on minimizing identification time and are unfair because in each round of identification, the same set of tags has to transmit more times compared to the other tags. In [17], Shahzad and Liu evaluated the fairness of their TH protocol along with other RFID identification protocols, and showed that TH achieves the highest fairness among all existing protocols. However, TH is not designed to achieve any required fairness; its design objective is to just minimize the identification time without fairness constraints.…”
Section: B Limitations Of Prior Artmentioning
confidence: 99%
See 3 more Smart Citations